Estimation of Combustion Engine Rotation Speed Based on Vibration Signal Analysis; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Avramchuk V. S. Valery Stepanovich (Mechanical Engineering Technology, 2016)
Title screen